A Study on Emotional Intelligence and Vocational Self-Esteem - BABAROGLU, Ayhan; Sangün, Levent (Advances in Social Sciences Research Journal, 2017)
The aim of this study was to investigate the relationship between vocational self-esteem and emotional intelligence. A total of 390 (188 women and 202 men) university students volunteered to participate in the study were included. Bar-On Emotional Quotient Inventory and Vocational Self-Esteem Scale as well as General Information Form were used to collect the data. As a result of the study, a positive and significant relationship was found between emotional intelligence and vocational self-esteem. This positive and significant relationship was also found for subscales of emotional intelligence. In addition, a positive and significant relationship was found between emotional intelligence and vocational self-esteem in terms of gender and the value processes don’t take place in emotional intelligence, men's professional self-esteem level is as twice as women’s vocational self-esteem level at the beginning, the increase in the vocational self-esteem level is greater in women when emotional intelligence is included in the process.